PENGARUH PENAMBAHAN POLYPROPYLENE FIBER MESH TERHADAP SIFAT MEKANIS BETON - Hasan, Hajatni; Tatong, Burhan; Tole, Joko (MEKTEK, 2013)
Polypropylene fiber is the fiber type of plastic (polypropylene) which is a special production with high technology. It is a chemical compound with the formula C3H6 hydrocarbons in the form of a single filamentor thin fibrous tissue shaped nets with a length of 6 mm to 50 mm and has a diameter of 8-90 microns. Thesefibers can be used to improve the performance of concrete.This research aims to determine how much influence the addition of polypropylene fibers on mechanicalproperties of concrete (compressive strength. split tensile strength and flexural strength). polypropylenefibers used doses of 0; 0.40 kg/m³, 0.60 kg/m³, 0.80 kg/m³ of concrete, which is made on the type of concretef'c 20 MPa with the value of water cement factor (FAS) at 0.53. Calculation of mixed concrete plans usingguidelines DOE (Department of Environment). The research location at Concrete and Building MaterialsLaboratory of the Faculty of Engineering, University Tadulako Palu. Specimens made as many as 72 piecesof 60 cylinders (D15 x 30 cm ³) and a beam of 12 pieces (15 x 15 x 60 cm ³). Specimen testing performed at28 days.Test results obtained fiber concrete compressive strength, split tensile strength and flexural strength, higherthan normal concrete. Compressive strength testing of optimum values obtained at doses 0.60 kg/m³. with anincrease of 3.62% compared to normal concrete. From testing split tensile strength and flexural strengthoptimum values obtained of each at doses of 0.65 kg/m³ and 0.58 kg/m³. For the split tensile strengthincreased 20.44% and flexural strength increased 11.26% compared to normal concrete. Keywords: polypropylene fibers. mechanical properties of concrete.